Intergenerational Mobility and Return Migration: Comparing sons of foreign and native born fathers - Christian Dustmann (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2005)
This paper studies the intergenerational mobility in earnings and education for father-son pairs with native and foreign born fathers. We develop a simple model which illustrates that a higher probability of a permanent migration of the parent increases educational investments into the child. Our empirical evidence is largely consistent with this. We find higher intergenerational mobility for father-son pairs with native born fathers than with foreign born fathers. For the foreign born, we find that son's permanent wages are strongly and positively associated with the probability of the father's permanent migration. Investigating investments into education, we find again a strong association between the probability of the father's permanent migration, and the son's educational attainments. These effects remain if in addition we condition on father's education, or on father's permanent earnings.
Keywords: 330